The Increasing Returns Revolution in Trade and Geography - Krugman, Paul (American Economic Review, 2009)
Thirty years have passed since a small group of theorists began applying concepts and tools from industrial organization to the analysis of international trade. The new models of trade that emerged from that work didn't supplant traditional trade theory so much as supplement it, creating an integrated view that made sense of aspects of world trade that had previously posed major puzzles. The "new trade theory"—an unfortunate phrase, now quite often referred to as "the old new trade theory"—also helped build a bridge between the analysis of trade between countries and the location of production within countries. In this paper I will try to retrace the steps and, perhaps even more important, the state of mind that made this intellectual transformation possible. At the end I'll also ask about the relevance of those once-revolutionary insights in a world economy that, as I'll explain, is arguably more classical now than it was when the revolution in trade theory began.